Islam dan KDRT (Tinjauan Hukum Islam terhadap Praktek Kekerasan dalam Rumah Tangga) - Abu Yazid Adnan Quthny (Fakultas Syariah Institut Ilmu Keislaman Zainul Hasan, 2016)
Cases of domestic violence are still a phenomenon that often happens in people’s lives. Not infrequently, the violence bears the physical suffering of the victim. The perpetrators of violence often defend themselves by aliby, what it does is the right guaranteed in culture and religion. In a patriarchal society, acts of domestic violence are often not an issue that is considered serious. Even sometimes the women shut acts committed partner because regarded as a disgrace husband. In Indonesia, the largest religious believer is Islam. However,in the last 10 years, the rate of domestic violence is quite alarming. Narrow religious understanding, as well as the permissive culture of women to acts of domestic violence to be one of the root causes of why the action is still ongoing. Islamic law, which in essence provides a high position for women, many reduced to justify acts of domestic violence.